Marginal Mandibulectomy Defect Rehabilitated with Cast Partial Denture: A Case Report - Pathak, B; Sitaula, BB; Parajuli, PK; Suwal, P (Journal of Nepalese Prosthodontic Society, 2023)
The primary prosthetic objectives for marginal mandibulectomy defects are to restore mastication, speech and appearance by replacement of teeth. With marginal resection of mandible followed by reconstruction with submental flap, the major prosthesis concern is related to soft tissue potential for support due to loss of vertical ridge height, loss of vestibular depth, mobility and displaceability of the flap that frequently unseats the prosthesis. This article describes prosthetic rehabilitation with a cast partial denture for missing teeth and restoring function for a patient who had undergone wide lesion excision of verrucous carcinoma with marginal mandibulectomy.